2012
DOI: 10.7314/apjcp.2012.13.10.5081
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Characteristics and Survival Analysis of Breast Cancer Molecular Subtypes with Hepatic Metastases

Abstract: (TN, P=0.11). In multivariate analysis, a 2 year-interval from initial diagnosis to hepatic metastasis, treatment with endocrine therapy, and surgery were independent prognostic factors. Endocrine therapy could improve the survival of luminal subtypes (P=0.004) and was a favorable prognostic factor (median survival 23.4 months vs. 13.8 months, respectively, P=0.011). Luminal A group of patients treated with endocrine therapy did significantly better than the Luminal A group of patients treated without endocrin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 18 publications
(23 reference statements)
0
17
0
Order By: Relevance
“…In addition, Eichbaum and colleagues (22) found a prognostic benefit for patients with a positive hormone receptor (HR) status and an expression of Ki-67 < 20%, p53 < 50%. However, Ge and colleagues (18) showed breast cancer subtypes were not associated with survival after liver metastases in 104 patients with breast cancer with liver metastases. Thus, the association of breast cancer subtypes and survival after liver metastases was unclear and remained controversial.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, Eichbaum and colleagues (22) found a prognostic benefit for patients with a positive hormone receptor (HR) status and an expression of Ki-67 < 20%, p53 < 50%. However, Ge and colleagues (18) showed breast cancer subtypes were not associated with survival after liver metastases in 104 patients with breast cancer with liver metastases. Thus, the association of breast cancer subtypes and survival after liver metastases was unclear and remained controversial.…”
Section: Introductionmentioning
confidence: 99%
“…Population-based estimates for the prognosis in patients with newly diagnosed breast cancer and liver metastases are lacking. Data from several single institution experiences and retrospective studies (8,(16)(17)(18)(19)(20)(21)(22)(23) yielded varying results. Duan and colleagues (23) reported on the outcome of 123 patients with breast cancer diagnosed with liver metastases; they found subtype remained an independent prognostic predictor among patients with breast cancer liver metastases, in which triplenegative breast cancer (TNBC) conferred the worst survival after diagnosis of liver metastases when compared with non-triplenegative subtypes.…”
Section: Introductionmentioning
confidence: 99%
“…While the progress has decreased death rates of breast cancer, the complexity of breast cancer and several genetic abnormalities has made it difficult. therefore targeting a single pathway for inhibiting the activity of one element is improbable to be effective (Zajac et al, 2010;Ge et al, 2012;Shawky et al, 2014). Identification of a molecular target that will modulate mechanisms of several signaling pathways would be suitable for anticancer therap (Zhang et al, 2012;Cihan 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Good prognosis with early metastasis was shown in a study by Qi Dong Ge, but in a study by Wyld et al [13][14] metastasis free interval had no effect on survival. This can be attributed to all nodes that other systemic metastases were seen in patients with long disease free interval to liver metastases.…”
Section: Discussionmentioning
confidence: 88%
“…It has been reported that nearly 30% of breast cancer patients will develop liver metastases along the duration of their disease. 1-2 Liver metastases usually develop in the terminal stage of breast Hepatic with brain 13 (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22) International Journal of Hematology and Oncology cancer, and are often accompanied by extrahepatic metastases. Isolated liver metastases are very rare (4%-5%).…”
Section: Discussionmentioning
confidence: 99%